2013
DOI: 10.1071/ch13269
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Arene Ruthenium(II) Complex as Apoptosis Inducer of A549 Cells

Abstract: An arene ruthenium(ii) complex coordinated with 2-(2-chlorophenyl)-1H-imidazo[4,5-f][1,10]phenanthroline, [(η6-C6H6)Ru(o-ClPIP)Cl]Cl (1), has been prepared by using microwave-assisted synthesis technology. The anti-tumour activity of this complex against various tumour cells has been evaluated by MTT assay and the results show that complex 1 exhibits selective inhibitory activity against the growth of human lung adenocarcinoma A549 cells with IC50 = 31.58 μM. Further studies by flow cytometric analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…87 The Ru(II) complex acts as a groove binder to the cmyc G4 DNA forming 1:1 complex. 84 The thermodynamic feasibility (negative value of ΔG) of Pu27−TPP complex formation is also reflected in the negative MMPBSA and MMGBSA values depicted in Table 2.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…87 The Ru(II) complex acts as a groove binder to the cmyc G4 DNA forming 1:1 complex. 84 The thermodynamic feasibility (negative value of ΔG) of Pu27−TPP complex formation is also reflected in the negative MMPBSA and MMGBSA values depicted in Table 2.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The binding affinity obtained is comparable to previously reported literature. 14 Small molecules like sanguinarine, 82 chelerythrine, 26 diarylethynyl amides, 83 arene ruthenium(II) complexes, 84 aryl indenopyrimidine derivatives, 85 and so forth, have similar binding affinity toward c-MYC G-quadruplex structures. The molecule TPP possesses a low K d (high K a ) value but causes a modest increase in ΔT m upon binding with Pu27.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10]phenanthroline, 18, Figure 5) was prepared with MAS heating of [Ru(η 6 -C 6 H 6 )Cl 2 ] 2 and o-ClPIP in dichloromethane at 60 • C for 30 min to obtain the product in higher yield (91%) than with traditional procedures [136].…”
Section: Ruthenium and Osmiummentioning
confidence: 99%
“…The results consistently suggest these complexes as prospective metal drugs for cancer chemotherapy. In our previous studies, arene Ru(II) complexes coordinated by phenanthroimidazole derivates displayed remarkable anti-tumor activity and low toxicity to normal cells [ 13 , 14 , 15 ]. Further investigation showed that this kind of arene Ru(II) complexes could suppress the proliferation, migration, and invasion of cancer cells by blocking the formation of invadopodia via inducing DNA damage and S-phase arrest [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%